2014
DOI: 10.1080/03004430.2014.957693
|View full text |Cite
|
Sign up to set email alerts
|

Social competence of Mandarin-speaking immigrant children in childcare

Abstract: This study aims to examine social competence of Chinese immigrant children and its associations with age, length of attendance in childcare, gender, generational status and proficiencies in English and Mandarin Chinese. One hundred Mandarin-speaking children aged three to five years from 15 childcare centres in Sydney were assessed by normed English and Mandarin tests. Childcare educators rated the children's social competence questionnaires. The results indicated that Chinese children performed well in social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…At the same time, my observations of the case study children suggested that their struggles with the English language were frequently very frustrating for them as was apparent when their inability to express themselves properly in English led them to lose control of their emotions and resort to behaviours such as crying, screaming, or similar vocalisations. This finding is in line with previous research linking children's self-regulation with their language skills (see Ebbeck et al, 2010;Nemeth & Brillante, 2011;Ponitz et al, 2009;Ren, 2015). My observational data also provided evidence of teacher practices to support children in handling their frustrations by acknowledging their feelings, giving them time to express themselves, and providing them with language models to solve their problems.…”
Section: Observational Datasupporting
confidence: 89%
See 2 more Smart Citations
“…At the same time, my observations of the case study children suggested that their struggles with the English language were frequently very frustrating for them as was apparent when their inability to express themselves properly in English led them to lose control of their emotions and resort to behaviours such as crying, screaming, or similar vocalisations. This finding is in line with previous research linking children's self-regulation with their language skills (see Ebbeck et al, 2010;Nemeth & Brillante, 2011;Ponitz et al, 2009;Ren, 2015). My observational data also provided evidence of teacher practices to support children in handling their frustrations by acknowledging their feelings, giving them time to express themselves, and providing them with language models to solve their problems.…”
Section: Observational Datasupporting
confidence: 89%
“…Throughout the conflicts, I was aware that the Middle Eastern children were struggling to express themselves verbally and, in some cases, resulted in behaviours like crying, screaming, or similar vocalisations indicating that not being able to articulate themselves in English was a very frustrating experience for them. This causal relationship has been noted in several previous studies (see Ebbeck et al, 2010;Nemeth & Brillante, 2011;Nykiel-Herbert, 2010;Ren, 2015). I also observed evidence that is congruent with the explanation above that conflicts were sometimes caused by children's attempts to make two sets of cultural norms match.…”
Section: Observational Datasupporting
confidence: 87%
See 1 more Smart Citation
“…Social networks ease newcomer children's transition processes and integration, thus contributing to the children's happiness and well-being. Additionally, advanced language competency aids children in feeling less nervous and more comfortable during their transition to a new atmosphere (Ren, 2015). Children who do not feel comfortable participating in social activities may experience social withdrawal, a condition in which children often forbear from social activities in the presence of peers.…”
Section: Children Social Adjustmentsmentioning
confidence: 99%